Moderating Effect of Board Structure on Equity Market Timing—Capital Structure Relationship of Indonesian Manufacturing Companies - Rahmat Setiawan; Acchedya Anugrahani (Ekonomi Bisnis, 2021)
Equity Market Timing is a relatively new capital structure theory taken by management to get sources of funds used by companies as corporate operational activities. This study examines and examines the effect of market timing equity as measured by using the (MTB) on capital structure as measured by using the book leverage ratio with the moderation of the board of directors structure. The sample used in this study was 80 companies. The data analysis method used is multiple regression. The results showed that MTB harmed capital structure. The moderating variable size of the board of commissioners and representatives of the board of directors weakens the negative impact of MTB on capital structure. An audit committee that did not measure the weaknesses or negative effects of MTB on capital structure.